The heart rate method for estimating oxygen uptake: Analyses of reproducibility using a range of heart rates from cycle commuting - Schantz, Peter (PLoS One, 2019)
Monitoring aerobic exercise intensities of free-living physical activities is valuable for purposes such as education and research. The heart rate (HR) method, based on the linear relation between HR and oxygen uptake (VO(2)), is potentially valuable for this purpose. Three prerequisites are that the method is reproducible, and valid for the specific form of physical activity executed as well as under field conditions. The aim of this study is to evaluate reproducibility of the heart rate method in the laboratory. VO(2) and HR measurements were made on two different occasions during three submaximal (model 1) plus a maximal exercise intensity (model 2) on a cycle ergometer in the laboratory. 19 habitual commuter cyclists (9 males and 10 females), aged 44 ± 3 years, were measured. The reproducibility of the estimated VO(2), based on three levels of HR from commuting cycling and the regression equations from test and retest were analyzed. Differences between the two models were also studied. For both models, there were no significant differences between test and retest in the constituents of the regression equations (y-intercept, slope and r-value). Neither were there any systematic differences in estimated absolute levels of VO(2) between test and retest. The relative differences between test and retest, based on estimations from three different levels of HR, were 0.99 ± 11.0 (n.s.), 2.67 ± 6.48 (n.s.) and 3.57 ± 6.24% (p<0.05) for model 1, and 1.09 ± 10.6, 1.75 ± 6.43 and 2.12 ± 5.92% (all n.s.) for model 2. However, some large individual differences were seen in both models. There were no significant differences between the two models in the slopes, intercepts or r-values of the regression equations or in the estimated levels of VO(2). The heart rate method shows good reproducibility on the group level in estimating oxygen consumption from HR-VO(2) relations in the laboratory, and based on three levels of HR which are representative for cycle commuting. However, on the individual level, some large variations were seen.